Numerical electromagnetic field analysis of lightning current in tall structures. - Baba, Y. (IEEE Transactions on power delivery)
The Numerical Electromagnetic Code (NEC-2) is applied to the electromagnetic analysis of tall structures hit by lightning. The advantage of the analysis using NEC-2 is that it can accurately compute the current distribution along a conductor system by the method of moments. The waveforms of the lightning currents measured on freestanding tall structures are well reproduced, and the computed waveforms of the electric and the magnetic fields at some distance from the structure hit by lightning agree fairly well with the measured waveforms. In the analysis, a lightning channel is represented by a vertical conductor that is loaded by series inductance and resistance so as to simulate the slow propagation velocity of a current wave on the lossy channel. This representation is demonstrated to be quite effective